Recurrent peripheral cemento-ossifying fibroma - Treville Pereira; Subraj Shetty; Arvind Shetty; Svylvy Pereira (Wolters Kluwer Medknow Publications, 2015)
Peripheral cement-ossifying fibroma (PCOF) is a rare osteogenic neoplasm that ordinarily presents as an epulis-like growth. It frequently occurs in maxillary anterior region in teenagers and young adults. We report a case of PCOF in a 42-year-old male, which was previously surgically excised and recurred after a period of 2 years. PCOF should be considered in the differential diagnosis of reactive hyperplastic lesions originating from gingiva. Hence, early diagnosis with proper surgical excision and aggressive curettage of the adjacent tissues is essential for prevention of recurrence.